Clinical course of Merkel cell carcinoma: a DeCOG multicenter study of 1049 patients - Lodde, Georg Christian; Leiter-Stöppke, Ulrike; Gesierich, Anja Heike; Eigentler, Thomas; Hauschild, Axel; Pföhler, Claudia; Gambichler, Thilo; Herbst, Rudolf; Meier, Friedegund; Hassel, Jessica C.; Meiß, Frank; Mohr, Peter; et al. (European journal of cancer, 2025)
Background - Merkel cell carcinoma (MCC) is a highly aggressive skin cancer with neuroendocrine differentiation characterized by frequent recurrences. Large epidemiological databases (e.g., SEER, IARC) lack granularity in analyzing associations between tumor, patient characteristics, locoregional interventions and recurrence patterns. - Patients and methods - Within the pre-immunotherapy era (1998-2017) the DeCOG MCC registry included 1049 patients with histopathologically confirmed MCC. Patient/tumor characteristics, treatment details, and outcomes were analyzed. Primary endpoints were progression-free probability (PFP) and disease-specific survival (DSS). - Results - Median age at diagnosis was 74 years; 50.4% were males. Primary tumors most frequently occurred on the head/neck (32.2%) and upper extremities (29.1%). One-third of patients presented with stage ≥IIIA disease. At a median follow-up of 10 years, 36- and 60-months PFP rates were 69.0% and 63.9%, respectively; DSS rates were 86.9% and 82.6%. Surgical margins of 1-2 cm provided the best PFP and DSS improvement; margins >2cm did not further improve clinical outcome. Similarly, for stage IIIA patients a complete lymph node dissection (CLND) did neither improve PFP nor DSS. Early radiotherapy (<8 weeks post-diagnosis) significantly improved PFP (HR 1.36) and DSS (HR 1.79). Expansion of radiotherapy to lymph node bed showed no additional benefit. Patients with multiple metastases at first recurrence had poorer DSS (HR 2.0) compared to those with single metastases, irrespective of locoregional or distant spread. - Conclusions - MCC outcomes are optimized with surgical margins of 1-2 cm and timely adjuvant radiotherapy. Larger margins, CLND in stage IIIA, or extended treatment radiation fields did not improve survival outcomes.